University proceedings. Volga region. Social sciences - N.V. Prokazina; Ya.A. Yukhnevich (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. In modern conditions, manifestations of discrimination in the labor market are quite common. One of the grounds for discrimination in modern society, in general, and in the labor market, in particular, is age discrimination – ageism. However, re-search into this problem and assessment of its real scale have certain limitations. Therefore, the study of problems of discrimination in the labor market from the standpoint of sociological analysis will allow us to assess the real nature, scale of discrimination in the labor market and identify the forms and features of manifestation. The purpose of the article is to identify the essential characteristics and features of ageism manifestation in relation to the younger generation in the labor market. Materials and methods. The conclusions and provisions are based on the results of international studies on the topic of ageism, the results of all-Russian studies of problems of discrimination based on age in the labor market and the results of the author's pilot study of ageism. The theoretical basis for the conclusions ob-tained was the theory of generations by W. Strauss – N. Howe and the concept of public opinion formation by Walter Lippmann. Results. The conducted analysis allows us to con-sider ageism as a social phenomenon that includes behavioral and emotional components based on the age stages of a person's life. It is argued that ageism manifests itself both in relation to representatives of the older and younger generations. The essential characteris-tics of ageism manifestation in relation to the younger generation are defined: disrespectful attitude on the part of older colleagues; disbelief in the formation of personal and professional qualities; an attitude towards lack of initiative, infantilism, irresponsibility of representatives of the younger generation; shifting routine and meaningless types of work to them; low level of trust. Conclusions. In the labor market, not only discrimination against older age groups is manifested. Today, ageism is noticeable in relation to the younger generation. A demand is being formed for research into ageism in relation to the younger generation as a manifestation of a form of discrimination in the labor market.